2020
DOI: 10.1002/mnfr.201901158
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic‐Based Approach to Identify Biomarkers of Apple Intake

Abstract: Scope There is an increased interest in developing biomarkers of food intake to address some of the limitations associated with self‐reported data. The objective is to identify biomarkers of apple intake, examine dose–response relationships, and agreement with self‐reported data. Methods and results Metabolomic data from three studies are examined: an acute intervention, a short‐term intervention, and a free‐living cohort study. Fasting and postprandial urine samples are collected for analysis by 1H‐NMR and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Measurements for biomarkers are available: citrate, hippurate, and proline betaine [ 19 ]. Full details on the study design and its participants are provided in [ 10 ]. While our model does not include study participants’ demographics it is worth noting that future work could examine how to incorporate information such as age and sex, as needed.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements for biomarkers are available: citrate, hippurate, and proline betaine [ 19 ]. Full details on the study design and its participants are provided in [ 10 ]. While our model does not include study participants’ demographics it is worth noting that future work could examine how to incorporate information such as age and sex, as needed.…”
Section: Resultsmentioning
confidence: 99%
“…The most common method used in clinical medicine to rapidly assess changes in magnesium status is the measurement of serum magnesium concentrations, but serum levels have little correlation with systemic magnesium levels or concentrations in specific tissues [10] . Some researchers have also chosen to use metabolites of foods as markers of certain nutrient intakes [66] . Some researchers use subjective dietary recall for dietary assessment [67] .…”
Section: Prospectivementioning
confidence: 99%
“…Another food item that has been subject to NMR foodomics studies is apple. McNamara et al [41] employed NMR metabolomics to analyze urine samples were collected 0, 2, 4 and 24 h after intake of apple, and NMR revealed that apple intake was associated with a pronounced increase in urinary concentration of xylose as well as acetylsalicylate. Xylose is among the main sugars found in apple, and the study demonstrates the potential of NMR foodomics in biomarker discovery.…”
Section: Specific Dietary Itemsmentioning
confidence: 99%